Suicide risk among Thai illicit drug users with and without mental/alcohol use disorders - Phunnapa Kittirattanapaiboon (2018)
Background: It is not yet known if the increased risk of suicide in substance abusers is caused by the causal and/or coexisting relationship between substance use and psychiatric disorders. This study was designed to estimate the suicide risk among individuals with illicit drug use alone, illicit drug users with mental disorders, and illicit drug users with alcohol use disorders. Methods: Subjects were participants of the 2008 Thai National Mental Health Survey. They were asked for their illicit drug use in the past year. The Mini International Neuropsychiatric Interview (MINI), current suicidality (1 month prior to assessment), mood episodes, anxiety disorders, psychotic disorders, and alcohol use disorders were used for assessing mental/alcohol use disorders. A score of 1 or more for the MINI-Suicidality module was defined as the presence of suicide risk. Results: Of the total 17,140 respondents, 537 currently used illicit drugs, while 1,194 respondents had a suicide risk. Common illicit drugs were kratom (59%) and (meth)amphetamine (24%). Compared with 16,603 Thais without illicit drug use, the illicit drug users with or without mental/alcohol use disorders (n=537) had an increased risk of suicide (adjusted odds ratio [OR], 95% confidence interval [CI] =2.09, 1.55-2.81). While those who used illicit drugs alone (no mental/alcohol use disorder) (n=348) had no increased risk of suicide (adjusted OR, 95% CI =1.04, 0.66-1.65), the illicit drug users with mental or alcohol use disorders (n=27 and n=162, respectively) had significantly increased risk of suicide (adjusted ORs, 95% CIs =14.06, 6.50-30.3 and 3.14, 1.98-4.99, respectively). Conclusion: A key limitation of this study was the combined suicidal behaviors as a suicidality risk. Mental or alcohol use disorders found in this population actually increased the suicide risk. These findings support the coexisting relationship that mental and alcohol use disorders play a vital role in increasing the suicide risk in illicit drug users. © 2014 Kittirattanapaiboon et al.